Application of Tissue Engineered Nanomaterials in Meniscus Sports Injury Repair - Han, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
In daily life and sports activities, the knee joint is the dominant joint. Movements such as walking upstairs, running, and walking require the knee joint to function. The principle of tissue engineering and the technical methods of molecular biology to construct functional meniscus replacement products in vitro have become an ideal method to fundamentally solve the meniscus injury. This paper aims to study the application of tissue engineered nanomaterials in meniscal sports injury repair. In this paper, KOA exercise therapy based on Kalman filter theory is proposed, which has a great effect on the rehabilitation of bone tissue injuries. The experimental results of this paper show that in the number of people with meniscus injuries in 2013, the percentage of people younger than 25 years old was 13%, and the percentage of people younger than 25 years old in 2020 was 12%, which did not change much. However, the percentage of people over 40 years old was 57% in 2013, and by 2020, the percentage is 66%. Although the increase is not large, the percentage of people over the age of 40 is the highest every year, which means that older people have a higher proportion of meniscal injuries.